STANDARDIZATION OF FLAX RAW MATERIALS: A COMPARATIVE ANALYSIS OF THE EXPERIENCE OF THE USA AND UKRAINE - KALINSKY, EUGEN; VORONKO, OLEXANDER (Herald of Khmelnytskyi National University. Technical sciences, 2024)
The main problem in the primary processing of bast fiber raw materials is Ukraine’s significant lag in the field of standardization compared to the USA, which negatively affects production efficiency, product quality, and competitiveness in the global market. The article aims to provide a comprehensive comparative analysis of flax raw material quality assessment systems in Ukraine and the USA, identify the key reasons for Ukraine’s lag, and develop practical solutions to address these issues. The research found that while Ukraine still relies on outdated standards for flax fiber quality evaluation, which are primarily based on organoleptic methods and do not take into account modern requirements, the USA is actively developing and implementing innovative standards that regulate a wide range of quality indicators, such as fiber fineness, strength, color, shive content, and other important parameters. The main reasons for Ukraine’s lag in the field of flax standardization include persistent economic difficulties, obsolete infrastructure and equipment, insufficient funding for scientific research, and weak integration with international standardization organizations. The authors propose a set of solutions to overcome these challenges, which involve increasing state support for the flax industry, intensifying research efforts aimed at developing new methods for assessing the quality of flax raw materials, harmonizing national standards with international ones, deepening international cooperation, and fostering the development of industry associations and clusters. The article emphasizes the necessity of introducing modern instrumental methods for assessing the quality of flax raw materials, such as spectrophotometry for color measurement, computer vision systems for analyzing fiber structure, and automated methods for determining fineness and shive content. The importance of developing standards for new and innovative flax products to expand the range, improve the competitiveness of domestic products, and enter promising markets is underlined.